1992
DOI: 10.1029/91jc00486
|View full text |Cite
|
Sign up to set email alerts
|

Collision of a loop current anticyclonic ring against the continental shelf slope of the western Gulf of Mexico

Abstract: A Loop Current anticyclonic ring --•330 km in diameter and extending to a depth of > 1500 m was observed to collide in January of 1984 against the continental shelf slope of the western Gulf of Mexico between 21.5 ø and 23øN. The collision occurred precisely at the time we conducted our Argos 84-1 hydrographic cruise in the western gulf (26o00 ' to 19ø20'N) aboard the R/V Justo Sierra. The Caribbean Subtropical Underwater (SUW) was used as a tracer to identify the Loop Current anticyclonic ring within the west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
1
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 20 publications
7
55
1
2
Order By: Relevance
“…1 Topographic map (with depth contours in meters) of the western North Atlantic Ocean and the maior currents and features of the region. The area of interest of this study, the WCS, is indicated by the arrow show the important interaction between eddies and shelf circulation have been done in regions such as the western Gulf of Mexico (Vidal et al 1992), but not in the WCS. Caribbean eddies have been studied in the past by observations and models (Carton and Chao 1999;Murphy et al 1999;Andrade and Barton 2000;Oey et al 2003), but their influence on the MBRS is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…1 Topographic map (with depth contours in meters) of the western North Atlantic Ocean and the maior currents and features of the region. The area of interest of this study, the WCS, is indicated by the arrow show the important interaction between eddies and shelf circulation have been done in regions such as the western Gulf of Mexico (Vidal et al 1992), but not in the WCS. Caribbean eddies have been studied in the past by observations and models (Carton and Chao 1999;Murphy et al 1999;Andrade and Barton 2000;Oey et al 2003), but their influence on the MBRS is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Both northward and temporary eastward movement of Loop current eddies in the western gulf have been observed [Kirwan et al, 1984;Lewis et al, 1989]. Upon colliding with the shelf break, anticyclonic eddies can shed a significant portion of their volume and angular momentum to the south, setting up adjacent cyclonic rings [Vidal et al, 1992]. Advection of shelf water offshore on the north side of a warm ring can also produce an adjacent cyclonic eddy as relative vorticity increases with flow into deeper water [Smith, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…After separation from the LC, these eddies travel westward until they dissipate due to processes not yet fully understood, which involve vertical mixing induced by air-sea fluxes and enhanced submesoscale activity around the rings' periphery, and interactions with other mesoscale structures and with the western boundary (e.g., Biggs et al 1996;Hamilton 2002;Vidal et al 1992Vidal et al , 1994LaCasce 1998;Mahadevan et al 2008).…”
Section: Introductionmentioning
confidence: 99%